MEMBRAN SELULOSA SEBAGAI MEDIA ULTRAFILTRASI UNTUK MENURUNKAN KADAR BESI DALAM AIR - - Faridah; - Efiana; - Saifuddin; - Jamaluddin (Jurnal Teknologi, 2014)
The contain of iron ions in  water causes the  water color become brownish yellow and water become also smelly. There are any ways that can be done to eliminate the iron ions in the water, one of them  is by using  membrane as a filter medium. This study offered cellulose membranes which is able to reduce iron levels  in water by using various types of cellulose membranes, such as celluose membrane I  derived from derived from sugar juice, cellulose membrane II from coconut water and cellulose membrane III which is derived from the combaining of sugar juice  and medium coconut water. After the cellulose membranes were produced, it  then was applied to reduce iron ions in water.  The samples were taken from water wells in Geudong area which have the iron inons around 0,203 ppm and water  drilled wells  in Politeknik Negeri Lhokseumawe  area which contains the iron ions around 0.184 ppm. After using the cellulose membrane as ultrafiltration  for both of samples, it was found that the iron  ions contain in water had reduced. The best  cellulose membrane to be used was the cellulose membrane II  which is derived  from coconut water. The effecency of iron reduction was founded in artificial (sampel III) sampel around 91,73%, following sampel I from Politeknik Negeri Lhokseumawe  around 68,75% and sampel II from Geudong area around 59,46%. The results showed that the membrane of coconut water is able to reduce iron in the water with higher efficiency than other membranes